Association of personal characteristics and cooking skills with vegetable consumption frequency among university students. (1st November 2021) - Bernardo, Greyce Luci; Rodrigues, Vanessa Mello; Bastos, Bianca Sabrine; Uggioni, Paula Lazzarin; Hauschild, Daniela Barbieri; Fernandes, Ana Carolina; Martinelli, Suellen Secchi; Cavalli, Suzi Barletto; Bray, Jeff; Hartwell, Heather; Pacheco da Costa Proença, Rossana
Abstract: Most university students are transitioning to adulthood, and tend to adopt unhealthy eating habits characterised by a low intake of fruits and vegetables. Few studies have specifically addressed the consumption of vegetables, which have a high content of minerals, fibre, and active compounds. The aim of this investigation was to assess vegetable consumption frequency among university students in a Brazilian capital and examine associations with individual characteristics and cooking skills. This crosssectional study used a online questionnaire to collect data. Cooking skills were evaluated in eight dimensions. Vegetable consumption was recorded in five frequency groups and then categorised into daily and non-daily consumption. Data were subjected to Pearson's chi-squared or analysis of variance followed by Bonferroni post hoc test. Associations between cooking skill dimensions and daily vegetable consumption were identified by crude and adjusted logistic regression analyses.Adjustment was performed for sex, age, paternal education, and overweight/obesity.Results are expressed as odds ratios (p < 0.05). Less than half of the respondents (N = 237; 45%) reported consuming vegetables daily. Higher level of paternal education, not being overweight or obese, and higher scores on seven cooking skill dimensions were positively associated with daily vegetable consumption. Given the scarcity of research on the topic, the findings of this study make a significant contribution to knowledge and may support public health strategies for promoting vegetable consumption among university students.